(untitled) (Journal of the College of Languages (JCL), 2019)
Style of Dostoevsky - it is a style that clearly emerges the desire for stimulating thought reader stage. It’s a style calculated to provoke the reader to their findings, conclusions and reflections. Dostoevsky hints, expressed as like inaccurate and at the same time with some startling sophistication. It makes the readers think and draw their own conclusions. Аннотация Стиль Достоевского - этостиль, в которомясноотмечаетсястремлениек стимулированиюзаконченного мыслячитателя. Этостильвызвать у читателя свои выводы, размышления и заключения. Достоевскийпоказывается, намекаеткак бы точно и в то же время скакой-тоудивительнейточностью. Он вынуждаетчитателя думать и делатьрезультаты. Ключевые слова: Достоевский, стиль, язык, монолог, полифония, индивидуализация, противоречие.